"Certain Vague Hopes of Disaster": A Psychosemiotic Reading of Alice Munro’s "The Found Boat" as the Flooding Text - Sellwood, Jane (Studies in Canadian Literature, 1992)
"The Found Boat" by Alice Munro foregrounds the cultural inscription of its female subject by the phallocentric society in which she lives – a twentieth-century Canadian small town with clearly delineated traditional gender roles. The female subject undergoes the repression and definition by lack necessary in the traditional psychoanalytic view for her entry into the symbolic order; however, Munro uses a strategy of paradox and its exposure of the split image of gender in the female subject to resist this episteme. Julia Kristeva’s theory of the paradoxical desire to reify and subvert authoritarian structures of language and literature serves to illustrate the ironic positioning of Munro’s work. Munro’s text posits a "lie": mimicking realist literary convention and the psychoanalytic tradition, "The Found Box" implicates itself, like its opening image of the Flood, in paradox’s subversion of authority.